Endoscopic injection of bulking agent around the ejaculatory ducts at the verumontanum for recurrent paediatric epididymitis. Issue 5 (October 2018) - Faure, A.; Haddad, M.; Hery, G.; Merrot, T.; Guys, J.-M.
Summary: Introduction: Paediatric recurrent epididymitis is frequently observed in several urogenital conditions, and may result in deterioration of long-term fertility. The management of recurrent epididymitis is still a therapeutic challenge for paediatric urologists, and as yet there is no consensus for treatment. Objective: To present a minimally invasive endoscopic approach for the treatment of recurrent epididymitis (more than three episodes). Patients and methods: Eleven boys were referred with a history of recurrent epididymitis in a context of urogenital malformations. All children underwent endoscopic transurethral injection. Dextranomer/hyaluronic acid was injected around the ejaculatory ducts at the verumontanum (Summary Fig.). The medical records and outcomes of the patients were retrospectively reviewed. Results: Of the 11 boys, two (18%) had a history of bladder exstrophy, three (27%) anorectal malformation, two (18%) peno-scrotal hypospadias, two (18%) posterior urethral valves, one (9%) seminal vesicle cyst, and one (9%) urethral stricture. The median age at injection was 3.75 years (range 8 months–14.7 years). Endoscopic injection effectively prevented recurrence in eight patients (73%) with a mean follow-up of 3 years (range 6 months–8.8 years). The mean injected volume was 0.7 ml/session. No perioperative complications were recorded. Vas clipping was performed in three patients after unsuccessful injections. Discussion: The current discussion for management of recurrent epididymitis is mainly based on vas clipping. Endoscopic injection in the verumontanum could offer several potential advantages over vas clipping; moreover, it is easy to perform for an urologist who usually uses endourological approaches. It is believed that only Kajbafzadeh et al. have reported their experience with endoscopic injection in the verumontanum in seven patients with structural anomalies, and they had a 42% success rate. Similarly, the current study did not observe perioperative or postoperative complications. Conclusion: In this series, endoscopic injection of the verumontanum was considered to be a safe and effective treatment in almost 73% of children with recurrent epididymitis. It did not result in perioperative complications and not contraindicate a subsequent surgical procedure such as vas clipping.